PANGGUNG KEBERAGAMAN: MENGULIK DIVERGENSI TRADISI DALAM PERAYAAN IDUL FITRI DI YOGYAKARTA DAN BANYUWANGI - Ariestianti, Intan (Studi Budaya Nusantara, 2024)
Tolerance and diversity in Indonesia are valuable assets and integral parts of the nation's identity. Cultural, religious, ethnic, and linguistic diversity has become a hallmark that enriches Indonesia's social and cultural panorama, laying a strong foundation for fostering social harmony and peace amidst religious and belief diversity. This is reflected in the principle of Bhinneka Tunggal Ika, which embodies the spirit of Indonesian nationalism. This article aims to explore a deep understanding of how local traditions and cultural diversity are reflected in the celebration of Eid al Fitr in both regions. The article will present various aspects influencing the differences in Eid al-Fitr celebrations, including history, local traditions, customs, and other socio-cultural factors. The method used in this qualitative research is interview instruments. This article conveys the message of the importance of respecting and celebrating cultural diversity within Indonesian society.